Undrained Shear Behavior of Samples Disturbance of Unsaturated Expansive Clay Soils: سلوك القص غير المصرف لاضطراب عينات تربة انتفاخية مشبعة جزئياً بالماء - Nariman Hisham Halalo (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2021)
Most Expansive Clay soils are sensitive to the disturbance in their internal structure as a result of the extraction of samples, because of the destruction in the natural soil structure. so a change in the properties of the expansive soil happens. This matter must be more precisely defined in the design of the foundations of engineering facilities. This paper presents a laboratory investigation of the influence of simulated sample disturbance on Shear Strength Parameters i.e. (internal friction angle and soil cohesion) by varying their plasticity and method of remolding samples using the direct shear test. Comparisons between simulations and experimental results showed that the behavior of the partially saturated expansive clay soil influenced by the method of remolding samples and is achieved through the relationship between stress and deformation. The disturbance of soil structure due to low shear strength parameters for soil, as the amount of change of the disturbance samples due to the decrease in values of both soil cohesion and the internal friction angle. In addition to that, the decrease in low plasticity soil PI (6%), is higher than the high plasticity soil (PI = 32%) due to the existence of Montmorillonite and kaolinite minerals in high plasticity soil which have high water absorption and cohesion, that preserving the shape of the soil sample.